2020
DOI: 10.1017/dmp.2020.33
|View full text |Cite
|
Sign up to set email alerts
|

Research on Disaster Literacy and Affecting Factors of College Students in Central China

Abstract: Objectives: Disaster literacy, which is a concept involved in moral quality, knowledge, and ability, impacts the disaster response. This study aimed to evaluate disaster education needs and to determine the affecting factors of disaster literacy among college students. Methods: A cross-sectional study was conducted through questionnaires. A total of 7200 college students from 10 colleges and universities in 5 provinces and cities in China were investigated. Results: Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
(17 reference statements)
0
9
0
3
Order By: Relevance
“…Based on the actual situation, the Ministry of Education should formulate the teaching plan and education outline of disaster nursing and compile appropriate teaching materials. 67 Additionally, hospitals should provide personalized disaster nursing education and training for emergency nurses with different educational levels.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the actual situation, the Ministry of Education should formulate the teaching plan and education outline of disaster nursing and compile appropriate teaching materials. 67 Additionally, hospitals should provide personalized disaster nursing education and training for emergency nurses with different educational levels.…”
Section: Discussionmentioning
confidence: 99%
“…Even so, earthquakes are a common phenomenon in Indonesia. In addition, according to [24] student disaster literacy is often poor due to a lack of disaster prevention and aid exercises and disaster reduction efforts. The same study was also conducted by [25] explaining that students' disaster mitigation literacy was at level 3 because the problem-based learning process was running very well.…”
Section: Discussionmentioning
confidence: 99%
“…However, mitigation was often closely aligned with disaster preparedness. For example, several studies tested students on their preparedness knowledge outside of the context of a specific disaster event (Gouramanis and Morales Ramirez 2021; Thorup-Binger and Charania 2019; Zhang et al 2021). These studies not only addressed students' personal preparedness knowledge but also provided crucial information to the universities on how to better mitigate against negative impacts on students and their families.…”
Section: Quantitative Analysismentioning
confidence: 99%
“…Disaster literacy and prior disaster knowledge may play a role in disaster risk perception, preparedness action, and protective behavior (Fadilah et al 2020;Greer et al 2018). For example, Zhang et al (2021) identified that in China, their sample of college students had relatively low levels of disaster literacy, but factors such as disaster experience, disaster training experience, and family disaster preparedness influence college students' disaster literacy. Similar findings have been found in both Indonesia (Aksa et al 2020) and India (Bhat et al 2017).…”
Section: College Students' Disaster Preparedness and Literacymentioning
confidence: 99%